2010
DOI: 10.1177/070674371005500906
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Risk of Depression with Sexual Risk Taking among Adolescents in Nova Scotia High Schools

Abstract: Objective: Several interrelated factors, including depression, influence adolescents' chances of risky sexual behaviour. We examined the relation between depression and sexual risk-taking behaviours in adolescents after accounting for the effects of other variables. Method:We surveyed male (n = 1120) and female (n = 1177) adolescents at 4 high schools in central Nova Scotia, measuring factors known to be associated with sexual risk taking. Risk of depression was assessed using the Center for Epidemiologic Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…Several studies have reported associations between low school connectedness and depression, whereas depression in adolescents also is associated with sexual risk behaviors . Depression was measured using an 8‐item version of the Center for Epidemiological Studies Depression Scale (CES‐D; range 0 to 24, Cronbach's alpha for this sample = 0.91) with a higher score signifying increased depressive symptoms, using a cut point of 7 or above to indicate a higher risk of being depressed over the previous 7 days .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported associations between low school connectedness and depression, whereas depression in adolescents also is associated with sexual risk behaviors . Depression was measured using an 8‐item version of the Center for Epidemiological Studies Depression Scale (CES‐D; range 0 to 24, Cronbach's alpha for this sample = 0.91) with a higher score signifying increased depressive symptoms, using a cut point of 7 or above to indicate a higher risk of being depressed over the previous 7 days .…”
Section: Methodsmentioning
confidence: 99%
“…3,4 During this period, adolescents spend much of their time in school, and school is felt to play a substantial role in whether they are at risk for, or protected from, various negative health and social outcomes. 5 School connectedness is viewed as whether students feel accepted, respected, included, and supported by others at school.…”
Section: Limitationsmentioning
confidence: 99%
“…It is now well established that lower mood, or affect, is associated with increased sexual [18,19] and health risk taking [20]. While less is known about changes in financial risk taking and mood, we know that positive mood states have been associated with more conservative behavior in risky tasks involving financial rewards [21][22][23].…”
Section: Risk Attitudementioning
confidence: 99%